METAPHOR AND ITS INTERPRETATION PROCESS IN DYSTOPIAN FICTION - Khvedelidze, Tamar (Online Journal of Humanities ETAGTSU, 2023)
This paper explores creative metaphors in dystopian narration. In addition, the implementation of a dystopian creative metaphor by an author and its interpretation process by an audience are examined. The empirical data employed for analysis were taken from “The Handmaid’s Tale” by M. Atwood and the comparative method was used to analyze the findings. Theoretical analysis was based on “Pictorial and Multimodal Metaphor” by Forceville (2006), “Metaphor, Simile, Analogy, and the Brain” by Riddel (2016), and "Reading Utopia, Reading Utopian Readers" by Roemer (2003). The goals of the paper are as follows: To show the significance and role of metaphor in dystopian narration. To discuss linguistic characteristics of dystopian narration. To reveal the subcategories of dystopian creative metaphors explored in the study and define the specific characteristics of their creating process, expressive forms, and interpretation features. The empirical data of this paper embrace the relevant examples from the novel and the TV show. Full Text (PDF)